Oxygen consumption and the evolution of order: negentropy criteria applied to the evolution of ants - Jaffe, K.; Hebling-Beraldo, M. J. [UNESP] (Springer Nature, 1993)
Optimization of energy use by evolving organisms, predicted by theoretical extensions of the neo-Darwinian theory, i. contrasted with that of irreversible thermodynamics, which predicts an increase in orderliness and thus an increase in energy consumption per unit of biomass. We compared this index with estimates of social complexity among ant genera and species. Our results show that simple optimization models cannot explain experimental data, and that social complexity correlates differently with negentropy at different levels of analysis. Comparing the genera among Formicidae, workers (not colonies) from genera with highly social species are less negentropic than those of socially primitive ones. At the sub-generic level, social complexity correlated positively with negentropy among species, for major workers in Acromyrmex and for minor workers in Atta. The results illustrate the complexity of thermodynamic criteria in the study of evolution but also hint at their usefulness. In this case, they show that two different evolutionary routes to the complex Attini ant societies may exist. © 1993 Birkhäuser Verlag Basel.
Keywords: ants; dissipative systems; energy; Negentropy; oxygen consumption; self-organization; social evolution